Adopting or resisting 24-hour news logic on evening bulletins? The mediatization of UK television news 1991−2012. (October 2015) - Cushion, Stephen; Lewis, Rachel; Roger, Hugh
This study carries out a longitudinal content analysis of United Kingdom (UK) fixed time evening news bulletins between 1991 and 2012 (N = 2040) in order to systematically examine whether they have adapted their format for the rolling news age with more live and instant conventions. Drawing on the concepts of mediatization and journalistic interventionism to interpret editorial changes, our findings broadly indicate that the media logic shaping bulletins has changed from reflecting the 'day's news' to covering more 'news as it happens' (as news channels now claim). We found an increasing reliance on less pre-scripted material and greater emphasis on live reporting from journalists (rather than external sources) who were routinely asked to instantly react, update, and interpret news, particularly in the world of politics. We suggest this represents a mediatization of television news bulletins, with broadcasters increasingly subscribing to a journalistic logic associated more with 24-hour news values than fixed time programming.